Analisis Penerapan Manajemen Kualitas Sumber Daya Manusia Dalam Proses Produksi Pada Umkm Batik Salsa Untuk Meningkatkan Daya Saing - Shendi Salsabila Hadi Nata; Elvina Eka Septi Cahyani; Danang Prayogo; Elok Rosyidah (GLOBAL SCIENTS PUBLISHER, 2025)
This research is motivated by issues of low human resource (HR) competence at UMKM Batik Salsa, which affects product quality and business competitiveness. Key problems include limited technical skills, inconsistent work discipline, and insufficient structured training. This study aims to analyze the implementation of HR quality management in the production process and its role in strengthening the competitiveness of Batik Salsa. The research uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using Miles & Huberman’s interactive model. Findings show that HR quality management is applied through internal training, task allocation based on expertise, and continuous guidance by skilled workers and the owner. This approach improves accuracy, product consistency, and production effectiveness. Enhanced HR competence also contributes to stronger competitiveness through unique motifs, stable product quality, and increased customer trust.